Building a Customer Centric Business for Service Excellence and Competitive Advantage in the Singapore Banking Industry - Lim, Chee Hiong Daniel (2009)
The financial service industry has gone through some very significant business transformation over the past 3 decades. Government deregulation opened up markets, technological changes created new channel and product opportunities, and data capabilities driven by affordable technology gave financial institutions the ability to identify and reach customers in new ways.